2007
DOI: 10.1159/000110873
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium Level and Clinical Deterioration in Alzheimer’s Disease

Abstract: Background: Recent studies suggest that magnesium, which specially affects the N-methyl-D-aspartate receptor response to excitatory amino acids, may be a supportive therapeutic agent in Alzheimer’s disease. Objective: To investigate the relationship between magnesium levels and the cognitive test results and clinical stages of the patients. Methods: Thirty-seven patients (20 women, 17 men) and 34 controls were included in the study. The patients were staged according to Global Deterioration Scale (GDS) and Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 36 publications
1
45
0
1
Order By: Relevance
“…In addition, higher serum Mg concentration, resulting from increased protein catabolic rate, was observed among uremic patients [41]. Mg status imbalance may affect the N-methyl-D-aspartate receptor response to excitatory amino acids and ameliorated dopaminergic neurons in the substantia nigra [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher serum Mg concentration, resulting from increased protein catabolic rate, was observed among uremic patients [41]. Mg status imbalance may affect the N-methyl-D-aspartate receptor response to excitatory amino acids and ameliorated dopaminergic neurons in the substantia nigra [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The role of magnesium (Mg) in neurodegenerative disorders and its effect in AD have also been investigated. Mg appears to be decreased in AD patients in clinical and autopsy studies (15,116).…”
Section: Von Bernhardi and Eugeni´nmentioning
confidence: 99%
“…One of the important activities of magnesium in the brain is its effect on NMDA (N-methyl-D-aspartate) receptors, which are ionotropic receptors of glutamate (9,10). In various concentrations, magnesium has different effects on the central nervous system and intellectual and neuronal functions by biochemical and neuronal modulation (11). Previous studies have suggested that the magnesium ion is a positive regulator of synaptic plasticity because it increases the number of pre-synaptic release sites, resulting in increased synaptic transmissions and improvements in learning and memory (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In various concentrations, magnesium has different effects on the central nervous system and intellectual and neuronal functions by biochemical and neuronal modulation (11). Previous studies have suggested that the magnesium ion is a positive regulator of synaptic plasticity because it increases the number of pre-synaptic release sites, resulting in increased synaptic transmissions and improvements in learning and memory (11,12). However, magnesium does not easily pass through the blood-brain barrier and intravenous injections lead to small increases in the amount of these ions in the cerebrospinal fluid.…”
Section: Introductionmentioning
confidence: 99%